The impact of a national antimicrobial stewardship programme on antibiotic prescribing in primary care: an interrupted time series analysis - Balinskaite,V; Johnson,AP; Holmes,A; Aylin,P (Clinical Infectious Diseases, 2019)
Background: The Quality Premium was introduced in 2015 to financially reward local commissioners of healthcare in England for targeted reductions in antibiotic prescribing in primary care. Methods: We used a national antibiotic prescribing dataset from April 2013 till February 2017 to examine the number of antibiotic items prescribed, the total number of antibiotic items prescribed per STAR-PU (Specific Therapeutic Group Age-sex Related Prescribing Units), the number of broad-spectrum antibiotic items prescribed and broad-spectrum antibiotic items prescribed expressed as a percentage of the total number of antibiotic items. To evaluate the impact of the Quality Premium on antibiotic prescribing, we used a segmented regression analysis of interrupted time series data. Results: During the study period, over 140 million antibiotic items were prescribed in primary care. Following the introduction of the Quality Premium, antibiotic items prescribed decreased by 8.2%, representing 5,933,563 fewer antibiotic items prescribed during the 23 post-intervention months compared with the expected numbers based on the trend in the pre-intervention period. After adjusting for the age and sex distribution in the population, the segmented regression model also showed a significant relative decrease in antibiotic items prescribed per STAR-PU. A similar effect was found for broad-spectrum antibiotics (comprising 10.1% of total antibiotic prescribing), with an 18.9% reduction in prescribing. Conclusions: This study shows that the introduction of financial incentives for local commissioners of healthcare to improve the quality of prescribing was associated with a significant reduction in both total and broad-spectrum antibiotic prescribing in primary care in England.